Pengolahan Lindi Tempat Pemprosesan Akhir Sampah Talang Gulo Dengan Metode Elektrolisis - S, Guntar Marolop; Kalsum, Siti Umi; Yusiana, Venny; Putri, Nur Juliana (Universitas Batanghari Jambi, 2023)
The Talang Gulo control landfill waste final processing site (TPA) has been decommissioned and converted into a Sanitary Landfill TPA in the city of Jambi. Even though it has been deactivated, the waste resulting from the decomposition of waste at the TPA control landfill must be managed. One of the wastes that is managed is leachate. Before being released into the environment, leachate must be processed in leachate ponds so that the receiving environment is not polluted. Some of the leachate parameters that must be managed are mercury (Hg) and cadmium (Cd), because if these two parameters enter surface water they will have a negative impact on aquatic biota. The research is planned at the Batanghari University Engineering Laboratory. On a laboratory scale, the Hg and Cd parameters of leachate can be reduced using the electrolysis method. Electrolysis is an alternative method for processing leachate because the chemical reaction process using electrodes can reduce the Hg and Cd parameters. The hypothesis that can be taken is that the electrolysis method can reduce the Hg and Cd parameters of landfill leachate.